The application of botulinum toxin in the treatment of overactive bladder - Justyna Wojcik; Aleksandra Obuchowska; Alicja Ozga; Arkadiusz Standyło (Kazimierz Wielki University, 2020)
Introduction: Urinary incontinence is an involuntary, decision-dependent urination that leads to partial or complete emptying of the bladder. The causes include overactive bladder syndrome, which is diagnosed on the basis of clinical symptoms, such as urgency to urinate, increased frequency of voiding, nocturia caused by increased reactivity of the detrusor muscle. Treatment of this condition includes, but is not limited to, pharmacotherapy, behavioral therapy, and pelvic floor exercises. It is also possible to use an innovative method of local injection of botulinum toxin into the bladder. It inhibits the release of acetylcholine, which results in the inhibition of the contractile activity of the detrusor muscle. The aim of the study:                    The purpose of the systemic review was to collect and analyze material of application of botulinum toxin in the treatment of urinary incontinence caused by overactive bladder. Material and methods: The work is a review of the literature on the use of botulinum toxin in the treatment of overactive bladder, published in 2002-2020. Description of the state of knowledge: The use of the described method gives long-lasting results compared to pharmacotherapy. In addition, it eliminates the side effects caused by drugs because the administration of drugs is reduced or discontinued. The use of botulinum toxin has many more benefits than simply improving the lives of people affected by urinary incontinence. When selecting the therapy, one should also pay attention to possible side effects resulting from the use of the described drug.              Summary: Intravesical administration by means of botulinum toxin cystoscopy is a modern, safe, effective and minimally invasive method of treating urinary incontinence, possible on an outpatient basis, allowing to improve the urodynamic parameters. Side effects are very rare. The botulinum toxin serotype A used in this method is the most studied serotype used for therapeutic purposes. The conducted research shows that over 90% of women reported a clinically significant improvement in sexual function after using the method.